2021
DOI: 10.3390/pathogens10030357
|View full text |Cite
|
Sign up to set email alerts
|

Ross River Virus Infection: A Cross-Disciplinary Review with a Veterinary Perspective

Abstract: Ross River virus (RRV) has recently been suggested to be a potential emerging infectious disease worldwide. RRV infection remains the most common human arboviral disease in Australia, with a yearly estimated economic cost of $4.3 billion. Infection in humans and horses can cause chronic, long-term debilitating arthritogenic illnesses. However, current knowledge of immunopathogenesis remains to be elucidated and is mainly inferred from a murine model that only partially resembles clinical signs and pathology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 107 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Results from the present study confirmed that transmission of RRV in horses in SE QLD follows a seasonal pattern with seroconversion events only being detected between December and March consistently throughout a 3.5-year period and being associated with air temperature without time-lag. In contrast, epidemiological modelling using human notification data in QLD showed that human infection peaked between March and May with rainfall, relative humidity, and air temperature identified as risk factors with 0-3 months' time-lags [5,[17][18][19][20][21][22][23][24]. Year-round irrigation usage and filled water troughs on farms and in paddocks in this subtropical study area would provide ideal breeding grounds for mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from the present study confirmed that transmission of RRV in horses in SE QLD follows a seasonal pattern with seroconversion events only being detected between December and March consistently throughout a 3.5-year period and being associated with air temperature without time-lag. In contrast, epidemiological modelling using human notification data in QLD showed that human infection peaked between March and May with rainfall, relative humidity, and air temperature identified as risk factors with 0-3 months' time-lags [5,[17][18][19][20][21][22][23][24]. Year-round irrigation usage and filled water troughs on farms and in paddocks in this subtropical study area would provide ideal breeding grounds for mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of predictive models have been developed to identify environmental risk factors associated with increased RRV transmission. It appears that rainfall, with a lag period of 0 to 3 months, is the most frequently identified meteorological risk factor for RRV outbreaks in humans across Australia [5,[17][18][19][20][21][22][23][24]. Temperatures (both minimum and maximum) and relative humidity, with 1-2 months lags, were also frequently identified as environmental drivers for increased RRV notification in humans [18][19][20][21]23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RRV has recently been suggested to be a potential emerging infectious disease worldwide. RRV infection remains the most common human arboviral disease in Australia, with a yearly estimated economic cost of USD 4.3 billion [32]. The primary goal of this study was to identify small-molecule inhibitors against CHIKV, which may later be extended to identify broad-spectrum antivirals.…”
Section: Discussionmentioning
confidence: 99%
“…Ross River virus is also transmitted by mosquito bites and presents in a similar way to CHIKV with fever, polyarthralgia, myalgia and a rash being typical. The equine encephalitis viruses, in contrast, are associated with neurological signs as the virus predominantly targets the brain [6][7][8]. In the USA between 2012 and 2021 there were 111 confirmed cases of Eastern equine encephalitis virus infection in humans causing 46 deaths while hundreds of horses were also infected [9].…”
Section: Introductionmentioning
confidence: 99%